2022
DOI: 10.1007/s00167-022-06943-2
|View full text |Cite
|
Sign up to set email alerts
|

Endoscopically assisted reconstruction of chronic Achilles tendon ruptures and re-ruptures using a semitendinosus autograft is a viable alternative to pre-existing techniques

Abstract: Purpose Achilles tendon ruptures are termed chronic after a delay in treatment for more than 4 weeks. The literature advocates surgical treatment with reconstruction to regain ankle push-off strength. The preferred technique is, however, still unknown and is often individualized. This study aims to present the technique and clinical outcome of an endoscopically assisted free semitendinosus reconstruction of chronic Achilles tendon rupture and Achilles tendon re-ruptures with delayed representatio… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
13
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 10 publications
(14 citation statements)
references
References 45 publications
0
13
0
Order By: Relevance
“…Dear Editor, we have read recently published article, entitled Endoscopically assisted reconstruction of chronic Achilles tendon ruptures and re-ruptures using a semitendinosus autograft is a viable alternative to pre-existing techniques by Nilsson et al [1] with interest. However, as experts in the field of Achilles tendon reconstructions, we felt obligated to express our concerns about this publication.…”
mentioning
confidence: 99%
See 2 more Smart Citations
“…Dear Editor, we have read recently published article, entitled Endoscopically assisted reconstruction of chronic Achilles tendon ruptures and re-ruptures using a semitendinosus autograft is a viable alternative to pre-existing techniques by Nilsson et al [1] with interest. However, as experts in the field of Achilles tendon reconstructions, we felt obligated to express our concerns about this publication.…”
mentioning
confidence: 99%
“…With specific graft stabilization, the patients are able to walk without crutches from day 1 after the surgery. Complications: two out of 22 patients in the presented study [ 1 ] were treated with oral antibiotics. Does it mean that they had wound infection?…”
mentioning
confidence: 99%
See 1 more Smart Citation
“…Moreover, it has been proven that better repair effects through external implementation of growth factor and/or stem cell therapy (during the tendon healing) can be achieved [ 22 ]. Several authors presented restoration of full function of the operated Achilles tendon and the overall patient satisfaction when using semitendinosus tendon grafts [ 18 , 23 , 24 , 25 ] or gracilis tendon grafts [ 26 , 27 ]. However, to our knowledge, this is the first study which presents a detailed, versatile clinical, functional and isokinetic assessment of patients after Achilles tendon reconstruction.…”
Section: Discussionmentioning
confidence: 99%
“…However, to our knowledge, this is the first study which presents a detailed, versatile clinical, functional and isokinetic assessment of patients after Achilles tendon reconstruction. Multiple assessments, which described the outcomes of the Achilles reconstruction were based on two most popular subjective, patient-reported scales: Achilles tendon Total Rupture Score (ATRS) and American Orthopedic Foot and Ankle Society Score (AOFAS), combined with isokinetic tests or functional tests [ 15 , 16 , 17 , 18 , 19 , 22 , 23 , 24 , 25 , 26 , 27 ]. However, in these studies, a clear contradiction was observed between the subjective and the objective outcomes, which, in our opinion, might be the result of an insufficient number of the Achilles tendon parameters tested.…”
Section: Discussionmentioning
confidence: 99%